Persepsi Petani Di UPT. Bulupountu Jaya Kecamatan Sigi Biromaru Tentang Penggunaan Bahan Kimia Pada Tanaman Bawang Merah Dalam Mendukung Keamanan Pangan Di Kabupaten Sigi - Ilham Ilham; Faturrahman Faturrahman; Saka Samudin (Universitas Tadulako, 2020)
Farmers perception affect their behaviour in farming to produce agricultural products with high quality so that the food security can be maintained and to prevent the risk of being poisoned event the death caused by the use of pesticides. This research was aimed at finding out farmers’ of perception on the use of chemical substances of red onions and to find out the food security level of the red onion existed in Sigi Biromaru subdistrict. This research is conducted at UPT. Bulupountu Jaya, Sigi Biromaru Subdistrict which located in Sidera and Oloboju subdistrict of Sigi Biromaru, Sigi District. This is a descriptive study that employs quantitative method with primary and secondary sources data that was recorded and tabulated. The results of this study showed that the level perception of the farmers at UPT. Bulupountu Jaya, on the use of chemical substance for the red onion they cultivate can be classified as high, their level of education at UPT. Bulupountu Jaya is also low (Elementary school, Junior High School, and Senior High School), however the level of success in farming at UPT. Bulupountu Jaya is high considering the farmers’ long experience. Condition of Food security on the commodity of red onion products is safe in all variables (dosage use, time use, kinds and mixture of substances) the application is appropriate and classified as high.